Application of the Principles of Good Faith and Pacta Sunt Servanda in Unequal Construction Contracts: A Case Study of B2B Developer–Contractor - Augustinus Setijanto; Corina Permatasari; Nana Artahana; Join Hadamean; Peto Syamsul Alam; Arief Koeswanto; Prastiwo Anggoro; Tri Lisiani Prihatinah (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
The legal relationship between developers and contractors in business-to-business (B2B) construction contracts in Indonesia often shows a significant imbalance of power. Although formally the contract is made based on the principle of freedom of contract, substantively the legal relationship often deviates from the principles of fairness and balance that form the basis of contract law. This paper examines the application of two fundamental principles in contract law, namely good faith and pacta sunt servanda, which means that every agreement made legally is binding on the parties who made it (Article 1338 paragraph (1) of the Civil Code) in the practice of biased construction contracts, particularly when developers modify FIDIC standard contracts by removing or limiting clauses that are detrimental to their interests, such as the Dispute Avoidance/Adjudication Board (DAAB), the right to an extension of time (EoT), and the right to suspend payment. This study uses a normative-juridical approach with case and comparative analysis methods, examining actual practices between developers and contractors experiencing delays, variation orders, and payment delays. The results of the analysis show that the removal of these protective mechanisms not only creates the potential for structural default but also constitutes a violation of the principle of good faith in the implementation of contracts as stipulated in Article 1338 paragraph (3) of the Civil Code. Meanwhile, the pacta sunt servanda principle cannot be applied absolutely if the substance of the contract contains a striking imbalance and violates propriety (Article 1339 of the Civil Code). This paper offers an update in the form of a reinterpretation of the principle of good faith as a corrective instrument against exploitative clauses, as well as a proposal for the establishment of a national DAAB institution with proportional costs to uphold contractual justice. Thus, the application of contract law in construction contracts must be directed towards substantive balance and a fair relational relationship between developers and contractors, so that national development objectives can be achieved without causing protracted disputes.